Efecto de la intervención educativa sobre el nivel de conocimiento del uso de antibacterianos en la población del Sector III del centro poblado menor Alto Trujillo - La Libertad - Carranza Bocanegra, Liz Jakelyn (2012)
Educational Intervention performed on Lower Town Center, III sector of Alto Trujillo, Porvenir District , Province of Trujillo, La Libertad Department, which developed in two educational interventions, aimed at improving knowledge of the antibacterial effects of irrational use, resistance bacterial, to promote the rational use of antibacterials ,aimed at people who attended the activities scheduled in the Auditorium of Cultural Center of the neighborhood III sample consisted of 50 people, who answered a pre and post –test to assess the level of knowledge about the use of antibacterials. Of all the people with whom we worked, relative to pretest, no educational intervention, 14% showed a good level of knowledge, a regular level 42% and 44% reported low level of knowledge, but none showed an excellent level of knowledge, after making the educational intervention, we observed that 50% had an excellent level of knowledge, a level 36% good and 14% a regular level of knowledge. The educational intervention had a great impactin increasing the knowledge level on the appropriate use of antibacterial agents